WASTE MANAGEMENT AS A KEY FACTOR IN ENSURING THE RIGHT TO A HEALTHY AND SAFE ENVIRONMENT IN MONGOLIA - Maral Bold, (International Journal of Innovative Technologies in Social Science, 2025)
Waste management is a crucial aspect of ensuring the right to live in a healthy and safe environment as outlined in the Mongolian Constitution. The Law on Waste governs waste-related matters in the country. The effectiveness of any social development is determined by the legal framework and its implementation. The volume of waste in Ulaanbaatar city is growing annually, and any discrepancies in laws, regulations, or management practices can impact Mongolians' right to a healthy and safe environment.There are numerous factors contributing to the continuous increase in waste in Ulaanbaatar city each year, but the legal framework is crucial from a systemic viewpoint. Effective enforcement of the Waste Law would ensure that all citizens understand their obligations, comply with the law, and have the privilege of residing in a clean and secure environment. As per legislative regulations, the enforcement of the ratified law should be assessed every five years; however, the implementation of the Waste Law has not been reviewed since its inception to date.According to the 23rd report of the National Human Rights Commission on human rights and freedoms in Mongolia, the country scored 29.6 on the index measuring global implementation of sustainable environmental policies, placing it 155th out of 180 countries worldwide and 19th out of 25 countries in the Asia-Pacific region. The report evaluates the enforcement of 8 laws to assess citizens' right to live in a healthy and safe environment. This study highlights potential areas for enhancing the enforcement of the Waste Law and the waste management system in Ulaanbaatar, addressing factors that impact the ability to live in a healthy and safe environment.